(untitled) - Gary B. Shelly; Gary B. Shelly; Thomas J. Cashman; Jeffrey J. Quasney (Boston, MA, 2007)
For the past three decades, the Shelly Cashman Series has effectively introduced computers to millions of students, consistently providing the highest quality, most up-to-date, and innovative materials in computer education. Enjoy the proven step-by-step style and improved Office 2003 updates of the Shelly Cashman Series and enhance your Office application skills today!
Keywords: Microsoft Office Frontpage 2003